Empowerment, satisfaction, commitment and retention intention among women in the military the case of the Philippine Navy - Castillo, Michelle C. (2019)
State policies and programs in the Philippines have paved the way for more women to participate in the peace and security sector, particularly in the military, in recent years. These policies are incorporated in the larger gender and development (GAD) policy of the government. This article assesses whether the GAD policies and programs actually translate to the retention of female military personnel in the Philippine Navy, one of the three branches of service of the Armed Forces of the Philippines. It measures the satisfaction of female military personnel on policies on women empowerment and protection against sexual violence, together with job satisfaction and organizational commitment, and evaluates whether these factors have an effect in their decision to stay or leave the military
profession. The revised gendered model shows that the most significant factor affecting the intention of female soldiers of the Philippine Navy to stay is organizational commitment while job satisfaction has more direct and significant positive effect on organizational commitment, with satisfaction on women empowerment and participation having a direct
positive effect on both organizational commitment and job satisfaction. The female soldiers’ experience of sexual harassment in the organization lowers their level of satisfaction on the organization’s programs on women empowerment and participation.
Keywords: Women military personnel; Women military personnel -- Job satisfaction; Women military personnel -- Social conditions; Philippine Navy; Philippines. Armed Forces